2020
DOI: 10.52690/jadila.v1i1.21
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Professional Teachers’ Questions in EFL Classroom

Abstract: In English language classroom, teachers’ questions are important parts of teaching English language. Teachers need to know what kind of questions which potentially support students learning the target language. However, students did not actively participate in learning particularly when responding to teachers’ questions. To overcome this problem, it is important for teachers to modify their questions through some techniques in order to get students’ responses. This study reports the types of teachers’ question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This research finding shows the difference from Nevtria (2020). In her study, it was found that teachers at SMAN 5 Bengkulu applied only three out of the six levels, namely "remembering", "understanding", and "analyzing".…”
Section: Level Of Questions Asked By English Teachers On English Onli...mentioning
confidence: 79%
“…This research finding shows the difference from Nevtria (2020). In her study, it was found that teachers at SMAN 5 Bengkulu applied only three out of the six levels, namely "remembering", "understanding", and "analyzing".…”
Section: Level Of Questions Asked By English Teachers On English Onli...mentioning
confidence: 79%
“…One study by (Navtria et al, 2020;Rachmawaty & Ariani, 2019) examined the types of teacher questions in EFL classes in Turkey and found that the majority of questions were display questions. This finding is similar to the present study's results.…”
Section: Discussionmentioning
confidence: 99%